Bouvard et Pécuchet et la clôture - Anne Herschberg Pierrot (Flaubert: Revue Critique et Génétique)
This article follows the thread of “enclosure”, as a space and as a limit, in Flaubert’s Bouvard et Pécuchet. Flaubert constructs this encyclopedic and philosophical novel as a kind of geographical and social huis clos, where the debates of ideas and their social repercussionsare experienced. This will allow us to study some modes of sociability in Chavignolles.